Kidnap: Exploring Guilt and Its Impacts towards Individuality - Indah Sari Yosodiharyo (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
Crime films usually focus on solving criminal cases or exploring the victim’s story. This creative work that I make, however, follows the story of a criminal who is given a mission to kidnap the successor of a wealthy CEO but mistakenly kidnaps another person instead. He is captured in a dilemma whether to let her go, and his situation gets worse when he is given a new order to kill her. The story revolves around the criminal as the true motive is revealed. With the boundary of good and bad being questioned, this work hopefully reminds people to be less judgmental towards others. The theme in this work is how guilt changes a person’s personality and way of thinking. The psychology of guilt is used for the main theory in this work. The story is presented through the genre psychological suspense, which normally focuses on a crime and its complexity.